Clarification of Motu Proprio Mitis et misericors Iesus: CCEO Canon 748; 1087; 1359; and 1372 (Roman Replies and CLSA Advisory Opinions 2016, 2016)
A diocesan official wrote on behalf of his diocesan bishop to the Pontifical Council for Legislative Texts seeking guidance regarding two questions concerning the new motu proprio Mitis et misericors Iesus. The response of the President of the Council follows.